Time-trend analysis of female rates among certified surgeon specialists across 10 surgical specialties in Norway - Søreide, Kjetil; Hauge, Elen M.; Torkildsen, Cecilie Fredvik; Veen, Torhild; Aarsland, Martine; Kvaløy, Jan T. (Scandinavian journal of surgery, 2025)
Background and Aims: Gender balance in surgical specialization has received increased focus, as women have traditionally made up a minority in surgical specialties. Little is known about how surgical disciplines are approaching gender equity and balance in general and subspecialty surgery in Norway. The aim of this study was to explore gender distributions across surgical disciplines to investigate gender balance and changes over time. - Material and Methods: An observational, cross-national study derived from specialists statistics on board certification in Norway. We investigated gender balance for surgical disciplines for the time period 2008 to 2024. Temporal time trends were investigated for fiscal years 2010, 2015, 2020, and 2024. Statistical analyses were done by the Poisson regression for temporal trends and gender distribution. - Results: For the 10 surgical disciplines investigated, the total number (n) of surgical specialists increased by 33.3% during the period. Numerically, general surgery, gynecology, and orthopedics made up 72% of all surgeon specialists in 2024. The female rate increased from 20.2% to 36.2% across all surgical disciplines. The observed female rate in 2024 was the highest in gynecology (75% women) and the lowest in thoracic surgery (<10% women). Despite a significant increase (with P < 0.001) in the female rate in all specialties, only gynecology and breast-endocrine surgery achieved >50% female rate among specialist surgeons. - Conclusion: Considerable variation in the rate and speed of obtaining gender equity exists across surgical specialties, concerningly in some of the larger surgical specialties. Further investigations should focus on identifying and addressing factors influencing the recruitment and retention of women in surgical specializations.
Gesehen am 12.01.2026